O dvodelnosti Prešernovega soneta - Svetina, Peter (Jezik in slovstvo, 1998)
Prešern's Poezije includes 42 sonnets. The main devides of internal structuring in these sonnets are changing the theme and changing participants in a communicative event. Additionally, elements of syntactic organization areused, such as a sequence of dependent clauses, begining the sestet part with an independent sentence, structuring the text with the resultative conjunction tako ('thus') and the comparative tako kakor - tako ('same as - as well'), using a shift in verbal and syntactic modality, a change of tense or time relation, or negation. 34 sonnets are divided after the second quatrain, five after the first quatrain, one is undivided, one has three parts (4/43/4),and dividing line in one sonnet is vague.
Keywords: Prešeren, France, 1800-1849; Slovene; slovenščina; Slovene literature; slovenska književnost; sonet; pesniške oblike; literarne študije